Isolation and multilocus sequence typing of Borrelia burgdorferi from Ixodes scapularis collected from dogs in Ontario, Canada - Grace K. Nichol; J. Scott Weese; Katie M. Clow (BMC Research Notes, 2023)
Abstract Objective To identify the multilocus sequence typing (MLST) sequence types of Borrelia burgdorferi from Ixodes scapularis in Ontario, Canada. Results One hundred and eighty-five I. scapularis ticks were submitted from 134 dogs via participating clinics from April 1, 2019, to March 31, 2020. Seventeen MLST sequence types of B. burgdorferi were detected from fifty-eight cultured isolates from 21 ticks. The most common MLST sequence types were 12 and 16. Mixed infections of two MLST sequence types were detected in four ticks. Three sequence types (48, 317, 639) were new detections in Ontario.